2003
DOI: 10.1080/0265673031000063864
|View full text |Cite
|
Sign up to set email alerts
|

Heat- and 4-hydroperoxy-ifosfamide-induced apoptosis in B cell precursor leukaemias

Abstract: In the group of high risk childhood acute lymphoblastic leukaemia (ALL), very early and early relapses have a very poor prognosis with conventional chemotherapy alone. Remission induction in these patients is often hindered by drug resistance. Thus, intensifying chemotherapy strategies are required. Application of hyperthermia enhances efficacy of certain anti-neoplastic drugs such as ifosfamide. In this study, effects and molecular mechanisms of ifosfamide - and hyperthermia-induced apoptosis are investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…These responses were, in fact, closely linked temporally. Of note, our observation of caspase-9 activation with febrile hyperthermia appears unique, as numerous other studies have used acute levels of hyperthermia [Enomoto et al, 2001;Little and Mirkes, 2002;Choi et al, 2003;Mauz-Korholz et al, 2003;Zhang et al, 2003;Souslova and Averill-Bates, 2004;Yasumoto et al, 2004]. In contrast to the role we have defined for caspase activation in this MCF-7 model, the anti-oxidant BHA was without effect on TNF killing, with or without hyperthermia ( Fig.…”
Section: Discussioncontrasting
confidence: 74%
“…These responses were, in fact, closely linked temporally. Of note, our observation of caspase-9 activation with febrile hyperthermia appears unique, as numerous other studies have used acute levels of hyperthermia [Enomoto et al, 2001;Little and Mirkes, 2002;Choi et al, 2003;Mauz-Korholz et al, 2003;Zhang et al, 2003;Souslova and Averill-Bates, 2004;Yasumoto et al, 2004]. In contrast to the role we have defined for caspase activation in this MCF-7 model, the anti-oxidant BHA was without effect on TNF killing, with or without hyperthermia ( Fig.…”
Section: Discussioncontrasting
confidence: 74%
“…At a first glance, cisplatin shows the greatest enhancement in cell killing with heat among platinum(II) complexes [25,28,31,32]. Increased drug accumulation by hyperthermia is one of the mechanisms involved in increased cisplatin toxicity and induced apoptosis in many human tumour types [29,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations demonstrated that hyperthermia enhances the efficacy of chemotherapy. This enhancement was shown to be mediated by different apoptotic signaling pathways in tumor cells [6,7]. Our patient tolerated the above described therapy regimen well, although she was of very young age and presented with extensive pulmonary metastases.…”
Section: Discussionmentioning
confidence: 83%
“…Multiple studies have attempted to answer this question with conflicting results. Several series have described a worse prognosis for those who are younger at the time of diagnosis (under the ages of 10, 12, or 15 years) [1][2][3][4][5][6]. Other investigators have reported equivalent rates of survival between younger patients with osteosarcoma and patients who are in adolescence or young adulthood [7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%